Functionalization Of Corruption Laws In Criminal Judgment Rules - Amir Akbar Nurul Qomar; Amin Purnawan (Law Development Journal, 2020)
The purpose of this research is to review and analyze the functionalization of the Corruption Law in the decisions of criminal justice judges. The research method used is Sociological juridical method with descriptive research specifications. The data used for this research are primary and secondary data taken by field observation, interview, and literature study methods. The conclusion from the results of the research is that the decision of the Semarang District Court Number 25 / Pid.Sus-TPK / 2019 / PN Smg provides an overview of the judicial process which is at the court stage as a form of functionalization of the Corruption Law which spells out the flow of the trial in cases of criminal corruption collectively by a Head of District in Wonogiri Regency. In the decision taking into account the provisions of Article 12 letter e of Act No. 31 of 1999 in conjunction with Act No. 20 of 2001 concerning Eradication of Corruption.